2021
DOI: 10.1111/dme.14739
|View full text |Cite
|
Sign up to set email alerts
|

Non‐adjunctive continuous glucose monitoring for control of hypoglycaemia (COACH): Results of a post‐approval observational study

Abstract: Prior to the Continuous Monitoring and Control of Hypoglycaemia (COACH) study described herein, no study had been powered to evaluate the impact of non-adjunctive RT-CGM use on the rate of debilitating moderate or severe hypoglycaemic events. Research Design and Methods: In this 12-month observational study, adults with insulin-requiring diabetes who were new to RT-CGM participated in a 6month control phase where insulin dosing decisions were based on self monitoring of blood glucose values, followed by a 6-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…Participants in the ANSHIN study had fewer episodes of SH while using the G6 compared to the baseline SMBG period. This observation aligns with the COACH study that reported non‐adjunctive Dexcom G5 use was associated with reductions in hypoglycaemic events for patients with insulin‐treated T1D or T2D 8 . Hypoglycaemia mitigation may be partly attributable to CGM alerts and alarms that warn users of impending low glucose.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Participants in the ANSHIN study had fewer episodes of SH while using the G6 compared to the baseline SMBG period. This observation aligns with the COACH study that reported non‐adjunctive Dexcom G5 use was associated with reductions in hypoglycaemic events for patients with insulin‐treated T1D or T2D 8 . Hypoglycaemia mitigation may be partly attributable to CGM alerts and alarms that warn users of impending low glucose.…”
Section: Discussionsupporting
confidence: 84%
“…The 2017 REPLACE‐BG study further demonstrated that using CGM data in place of SMBG testing as the basis for diabetes treatment decisions was safe for adults with T1D. 7 In addition, the COACH 8 study and the DIAMOND 5 and MOBILE 9 randomized clinical trials demonstrated that CGM use improved glycaemic control in people with diabetes better than SMBG, including greater reduced HbA1c, fewer SH events and improved CGM‐based metrics.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Diabetic Medicine, the impact of realtime continuous glucose monitoring with alerts and alarms (rtCGM) on severe hypoglycaemia is reported. 3 Previous studies have demonstrated the impact of rtCGM on hypoglycaemia exposure 4,5 and severe hypoglycaemia has been shown to be reduced in adults with type 1 diabetes at highest risk, 6 but this study replicated the beneficial impact on severe hypoglycaemia in rtCGM-naïve participants with insulin-treated type 2 diabetes and shows that this clinically important impact can be achieved with regular phone contact. As remote support for people with diabetes becomes embedded, and sensor access increases these findings will be increasingly important and impactful, both clinically and for cost-effectiveness analyses.…”
Section: Variance Of Concernmentioning
confidence: 56%
“…Additionally, CGM glucose trend arrows provide additional contextual information above and beyond the reliability of any single data point from finger stick blood glucose testing, enabling individuals to see past and recent glucose levels and observe recent trends 373839…”
Section: How Does Cgm Compare With Finger Stick Blood Glucose Testing?mentioning
confidence: 99%
“…A 12-month observational study in 519 adults with insulin-requiring diabetes (types 1 and 2) observed a 63% reduction in frequency of hypoglycaemia compared with finger stick blood glucose testing 38…”
Section: How Does Cgm Compare With Finger Stick Blood Glucose Testing?mentioning
confidence: 99%